Sine Rule

## Sine Rule

The sine rule can be used for any triangle, whether right angles or not. Note that the letters relating to the side are opposite the corresponding letters for the angles, i.e. a and A; b and B and c and C. The rule is:

frac(a)(sin A) = frac(b)(sin B) = frac(c)(sin C)

Use the sine rule when any two sides and an angle, or two angles and a side are known, the sine rule can be used. The rule covers all three sides and all three angles, but normally you would only use two of the pairs.

The sine rule can also be used with the angles on top: frac(sin A)(a) = frac(sin B)(b) = frac(sin C)(c)

## Example 1

What is the value of the angle x? Give your answer to 1 decimal place. use the SIN rule frac(sin A)(a) = frac(sin B)(b) substitute frac(sinA)(12) = frac(sin 76)(15) x12 both sides sin A =frac(12 xx sin 76)(15) sin A =0.776 sin-1 both sides A = sin^-1 0.776 A = 50.917 to 1dp A = 50.9 unknown angle 180 - 77 - 43 =60 use the SIN rule frac(sin A)(a) = frac(sin B)(b) substitute frac(x)(sin 60) = frac(8)(sin 43) x = frac(sin 60 xx 8)(sin 43) x = 10.159 to 1 dp x = 10.2